3D printing natural conductive medical patch aerogel and preparation method thereof

Through 3D printing technology and conductive processing, natural conductive medical patch aerogels with excellent biocompatibility and conductive properties are prepared, which solves the problem that traditional materials are difficult to take into account both biocompatibility, mechanical properties and conductive properties, and achieves the following: Remarkable application effects in the fields of cardiac repair and other fields.

CN119303158APending Publication Date: 2025-01-14GUANGZHOU MEDICAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411471441.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Traditional medical patch materials are difficult to take into account biocompatibility, mechanical properties and electrical conductivity, which limits their application in complex human environments and the use of electrical stimulation therapy.

Method used

Using 3D printing technology combined with frozen casting and conductive treatment, a natural conductive medical patch aerogel with an ordered micron-scale honeycomb pore and carbonization treatment was prepared, and through various conductive treatment methods such as carboxymethylation , conductive polymer coating, metal nanoparticle doping, etc., to improve the conductivity and mechanical properties of the material.

Benefits of technology

It realizes the low density, high strength and excellent conductivity of the material, enhances biocompatibility and mechanical stability, and is suitable for the repair of cardiac tissue engineering infarction, significantly improving drug release efficiency and adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303158A_ABST
    Figure CN119303158A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D printing natural conductive medical patch aerogel and a preparation method thereof, and the aerogel realizes low density and high strength through freeze casting and multiple conductive treatment methods. The geometric structure and porosity are optimized by using CAD and deep learning algorithms, so that the effectiveness and stability in tissue engineering repair are ensured. The aerogel disclosed by the invention not only has excellent biocompatibility and environmental friendliness, but also is suitable for tissue engineering infarction repair and regenerative medicine, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomaterials, and in particular to a 3D printed natural conductive medical patch aerogel and a preparation method thereof. Background Art

[0002] As an important biomedical material, medical patches play a key role in clinical medicine and are mainly used to repair or replace damaged or missing tissue structures in the human body. An ideal medical patch should have multiple excellent properties such as high biocompatibility, mechanical strength and conductivity to ensure that it can effectively perform its functions in the complex human environment and minimize secondary damage to patients.

[0003] However, traditional medical patch materials often have difficulty achieving optimal performance in all of the above aspects. For example, although some materials have good biocompatibility, they cannot meet the requirements of long-term implantation due to insufficient mechanical strength; while other materials may cause discomfort to patients after surgery or increase the risk of complications due to their high density. In addition, traditional materials are often not conductive, which limits their use in application scenarios that require electrical stimulation therapy.

[0004] In order to solve the problem of high density and low mechanical strength of traditional medical patch materials, the methods used mainly include composite material design, introduction of micro-nanostructures, cross-linking technology, surface modification, multilayer structure design, bionic structure design, etc. Among them, bionic design refers to the technology of drawing inspiration from biological structures and functions in nature to design materials or systems with similar properties. Compared with traditional solutions, bionic design has the advantages of optimizing mechanical properties, high biocompatibility, multifunctionality, environmental adaptability, etc., and can take into account the advantages of multiple aspects. However, in the actual preparation and application process, bionic design often involves the integration of complex structures and multi-level functions, and the manufacturing process is complex. In addition, although natural materials have excellent biocompatibility and mechanical properties, they have defects in long-term stability and compatibility. Therefore, there is an urgent need for a medical patch material that has both biocompatibility, mechanical properties and conductive properties. Summary of the invention

[0005] The purpose of the present invention is to provide a 3D printed natural conductive medical patch aerogel and a preparation method thereof, so as to solve the problem that the above-mentioned medical patch materials cannot take into account biocompatibility, mechanical properties and conductive properties.

[0006] To achieve the above objectives, the first aspect of the present invention provides a 3D printed natural conductive medical patch aerogel, comprising ordered micrometer-scale honeycomb pores prepared by freeze casting and a lignin conductive network formed by carbonization treatment.

[0007] The present invention combines freeze casting and conductive treatment. The freeze casting is to carboxymethylate kapok cellulose to make it conductive, and then mix it with a hydrogel precursor liquid in a certain proportion. The mixed gel reagent is poured into a mold, and after the hydrogel is formed, it is placed on a copper table half immersed in liquid nitrogen, and the colloid is quickly frozen and placed at -20°C for 24 hours, so that the aerogel has a lower density and a higher strength. The conductive treatment refers to modifying the material by different chemical or physical methods to improve its conductive performance.

[0008] The second aspect of the present invention provides a method for preparing a 3D printed natural conductive medical patch aerogel, comprising the following steps: (1) Preparation of kapok fiber, carbonized wood block and carbonized fiber; (2) treating one or more of kapok fiber, carbonized wood block or carbonized fiber to be conductive; (3) mixing the kapok fiber, carbonized wood block or carbonized fiber after the conductive treatment with a polymer precursor solution, and then adding an initiator and a catalyst to polymerize to obtain a mixed solution, and adding the mixed solution into a mold for freeze casting to obtain a composite cellulose ice mold; (4) placing the frozen composite cellulose ice mold in a freezing solvent for hydrogen bond reconstruction to obtain a composite cellulose solution; (5) The composite cellulose solution is 3D printed and coated with a conductive layer to obtain a bionic material.

[0009] Preferably, in step (1), the kapok is crushed and placed in a sodium chlorite solution, and the pH is adjusted to between 4 and 5 with glacial acetic acid. The solution is stirred in a water bath at 75 to 80° C. until the solution turns white, and then filtered to wash the solid matter to obtain kapok fibers.

[0010] The present invention uses 3D printing technology and the concept of bionic cone snail structure to prepare an aerogel scaffold with a fractal tree structure, a honeycomb pore structure and a spiral fiber structure. The scaffold is deposited layer by layer and arranged in a direction, which promotes the reconstruction of interchain hydrogen bonds and enhances the overall strength and stability of the scaffold.

[0011] Preferably, in step (1), the wood block is cut into small pieces, heated to 600-800°C in an inert atmosphere for carbonization to obtain carbonized wood blocks; and the kapok is heated to 600-800°C in an inert atmosphere for carbonization to obtain carbonized fibers.

[0012] Preferably, in step (2), the conductive treatment process adopts at least one of the following methods: carboxymethyl modification, conductive polymer coating, metal nanoparticle doping, carbon nanotube or graphene doping, enzyme-catalyzed conductive modification, ionic liquid doping, nitrogen-doped carbonization, graphene oxide reduction treatment, self-assembled monolayer modification, electrochemical doping, plasma treatment, microwave-assisted modification, electrospray deposition, silane coupling agent modification, and sol-gel method.

[0013] Specifically, (1) Carboxymethylation modification: Carboxymethylation modification is to change the chemical structure of kapok cellulose by introducing carboxyl groups. It improves the conductivity and water solubility of aerogel by introducing carboxymethyl groups, thereby enhancing its biocompatibility and mechanical properties.

[0014] 3 g of kapok or wood cellulose (or wood block) was soaked in 5 g of 50% sodium hydroxide solution and stirred at room temperature for 1 hour. Subsequently, 0.2 g of 50% sodium chloroacetate solution was slowly added to the reaction system for carboxymethylation treatment to finally obtain conductive wood cellulose. The range of raw material addition in each treatment process is as follows: the addition amount of sodium hydroxide is 5 g to 15 g, and the addition amount of sodium chloroacetate can be adjusted between 0.1 g and 0.5 g to optimize the conductive performance and reaction effect.

[0015] (2) Conductive polymer coating: The surface of aerogel is coated with conductive polymers (such as polypyrrole, polyaniline, etc.) to form a conductive network, thereby improving its overall conductivity.

[0016] In the conductive polymer coating process, conductive polymer monomers, such as pyrrole or aniline, and oxidants, such as ammonium persulfate, are added to the conductive wood cellulose solution. At the same time, ferric chloride hexahydrate can be added as a catalyst to promote the polymerization reaction. Through the in-situ polymerization reaction, a uniform conductive polymer coating layer is formed, which significantly improves the conductivity of the material.

[0017] (3) Metal nanoparticle doping: By doping metal nanoparticles (such as silver, gold or copper) into aerogels, their excellent conductive properties can be used to significantly enhance the conductive properties of aerogels.

[0018] The conductive wood cellulose solution is mixed with a metal salt solution, and metal nanoparticles are deposited on the cellulose surface through a chemical reduction reaction to form a conductive layer.

[0019] (4) Carbon nanotube or graphene doping: Carbon nanotubes or graphene are doped into aerogel as reinforcing agents to form a three-dimensional conductive network. Since carbon nanotubes or graphene themselves have excellent conductivity, their conductive properties and mechanical strength are significantly improved.

[0020] Carbon nanotubes or graphene are uniformly dispersed in a conductive wood cellulose solution, and conductive composite aerogels are prepared by freeze drying.

[0021] (5) Enzyme-catalyzed conductive modification: Enzyme-catalyzed reactions are used to modify the conductivity of aerogels, thereby giving them biocatalytic activity and conductive properties.

[0022] Conductive enzymes (such as CuNiR, laccase) and corresponding substrates are added to the conductive wood cellulose solution, and conductive polymers are generated on the cellulose surface through enzyme-catalyzed reactions.

[0023] (6) Ionic liquid doping: Ionic liquids are introduced into aerogels to enhance their electrical conductivity and electrochemical properties while improving their stability.

[0024] Ionic liquid was added into the conductive wood cellulose solution, stirred evenly and then freeze-dried to prepare the conductive composite aerogel.

[0025] (7) Nitrogen-doped carbonization: The conductivity and chemical properties of aerogels can be adjusted through the nitrogen-doped carbonization process, thereby achieving better conductive properties.

[0026] Conductive wood cellulose is mixed with urea, dried and then carbonized in an inert gas environment to form nitrogen-doped conductive carbon aerogel.

[0027] (8) Graphene oxide reduction treatment: Graphene oxide is reduced and incorporated into aerogel to enhance its conductivity and improve its mechanical properties.

[0028] The conductive wood cellulose solution is mixed with graphene oxide, and a reducing agent is added. Through stirring reaction, the graphene oxide is reduced to a conductive graphene layer and coated on the cellulose surface.

[0029] (9) Self-assembled monolayer modification: A monolayer is formed on the surface of the aerogel through self-assembly technology to optimize its interface properties and improve conductivity.

[0030] The conductive wood cellulose solution is mixed with the self-assembled monolayer material, and a conductive monolayer is formed on the surface of the cellulose through a self-assembly process.

[0031] (10) Electrochemical doping: Conductive materials are introduced into aerogels using electrochemical methods to enhance their conductive properties through interfacial reactions.

[0032] Conductive polymer monomers (such as PEDOT:PSS) are added to the conductive wood cellulose solution, and the conductive polymer is deposited on the cellulose surface through electrochemical polymerization to form a conductive layer.

[0033] (11) Plasma treatment: Plasma technology is used to treat the surface of aerogel to improve its surface conductivity and adhesion. Plasma treatment technology is used to modify the surface of conductive wood cellulose to introduce conductive groups and enhance conductivity.

[0034] (12) Microwave-assisted modification: Microwave radiation is used to promote the chemical reaction of aerogels to achieve efficient conductive modification. Conductive wood cellulose is mixed with conductive polymer monomers or metal salt solutions, and microwave radiation is used to react to quickly generate a conductive coating.

[0035] (13) Electrospray deposition: The conductive material is uniformly deposited on the surface of the aerogel through electrospray technology to form a good conductive layer and improve its conductive properties. The conductive wood cellulose is placed in an electrospray deposition device and the conductive polymer or metal nanoparticles are deposited on the cellulose surface using electrospray technology to form a uniform conductive layer.

[0036] (14) Modification with silane coupling agent: The conductive wood cellulose solution is mixed with a silane coupling agent, and a silane layer containing conductive groups is formed on the cellulose surface through a silanization reaction.

[0037] (15) Sol-gel method: Conductive wood cellulose is mixed with conductive oxides (such as RuO, FeO, TiO 2、 ZnO, etc.) precursors are mixed to form a conductive oxide coating on the cellulose surface through a sol-gel process.

[0038] Preferably, in step (3), PEGDA is dissolved in deionized water to obtain a polymer precursor solution, the kapok fiber, carbonized wood block or carbonized fiber after conductive treatment is added to water to form a suspension, the suspension is added to the polymer precursor solution for ultrasonic dispersion to obtain a mixed solution, the mixed solution is pre-cooled at 4°C, and the initiator and catalyst are slowly added in an ice bath, and quickly transferred to a mold, and the mold is placed on a copper block half immersed in liquid nitrogen. After the mixed solution is completely frozen, it is stored at -20°C for 48 hours to obtain a composite cellulose ice mold.

[0039] Freeze casting, the conductive modified kapok cellulose and carbonized wood blocks are mixed evenly to form a composite cellulose solution. The mixed solution is poured into a mold and gradually frozen to -20℃ to -80℃ to form ice crystals, which produce orderly micron-scale honeycomb pores inside.

[0040] Preferably, in step (3), the mass volume ratio of PEGDA to deionized water is 1-5 g: 2-10 mL, the kapok fiber, carbonized wood block or carbonized fiber after conductive treatment is 1-5% of the mass of the suspension, the initiator is ammonium persulfate, the catalyst is tetramethylethylenediamine, and the volume ratio of the initiator to the catalyst is 10-20:1-2.

[0041] Preferably, in step (4), the freezing solvent is ethanol or acetone.

[0042] Preferably, in step (5), the 3D printing parameters are: room temperature, layer thickness of 50-150 μm, and printing speed of 5-25 mm / s.

[0043] The present invention optimizes 3D printing parameters through deep learning, and the deep learning optimization is: Data collection and preprocessing: Collect geometric structure and mechanical property data of various 3D printed aerogels and perform data preprocessing; Deep learning model training: Use deep learning algorithms (such as convolutional neural networks (CNNs) and generative adversarial networks (GANs)) to train data and optimize the design parameters of aerogels. Use tools such as Python and TensorFlow to train models, and set parameters including the number of convolutional layers, learning rate, batch size, etc.

[0044] Optimize design: Optimize the geometry and porosity of the aerogel scaffold based on the predictions of the deep learning model. Optimize the printing quality by adjusting parameters such as printing path, layer thickness, and printing speed.

[0045] Verification and adjustment: Verify the effect of the optimized design through experiments, and further adjust the deep learning model and design parameters to ensure that the performance of the final aerogel scaffold is optimal.

[0046] Furthermore, the bionic structure simulates the biological structure in nature to optimize the mechanical and functional properties of the material. Specifically, the following steps are included: (1) Data collection and preprocessing Collect geometric structure and mechanical property data of various 3D printed aerogels. These data include different printing parameters (such as layer thickness, printing speed, printing path, etc.) and the performance indicators of the final aerogel (such as compressive strength, elastic modulus, etc.). The collected data is preprocessed, including removing outliers, standardization and normalization, to facilitate the subsequent training of deep learning models.

[0047] (2) Deep learning model training The preprocessed data was trained using deep learning algorithms such as convolutional neural networks (CNN) and generative adversarial networks (GAN). Using tools such as Python and TensorFlow, parameters including the number of convolutional layers, learning rate, and batch size were set to optimize the design parameters of the aerogel. During the training process, cross-validation was used to ensure the robustness and accuracy of the model, thereby improving the prediction performance of the aerogel.

[0048] (3) Optimized design Based on the predictions of the deep learning model, the geometry and porosity of the aerogel scaffold were optimized. The printing quality was improved by adjusting parameters such as the printing path, layer thickness, and printing speed. Specifically, the design of the bionic cone snail simulates the complex fractal structures found in nature to optimize the mechanical and functional properties of the material. The design of the structure not only enhances the conductivity of the aerogel, but also improves its mechanical properties, making it more suitable for biomedical applications.

[0049] (4) Verification and adjustment The effect of the optimized design was verified by experiments, and the performance indicators of the aerogel scaffolds before and after optimization were compared. The tests included compressive strength, toughness, and conductivity to ensure that the final aerogel scaffold achieved optimal performance. The experimental results showed that the optimized cone snail microneedle structure had significant improvements in mechanical properties and drug release efficiency. In addition, by further adjusting the deep learning model and design parameters, the biocompatibility and mechanical stability of the final product were guaranteed.

[0050] (5) Implementation examples and technical effects The effectiveness of the optimized design was verified through experiments on mice and rats, and the application effect of aerogel scaffolds in cardiac tissue engineering infarction repair was specifically evaluated. The experimental results showed that the optimized aerogel scaffolds showed good effects in promoting tissue regeneration and could effectively improve the repair capacity of infarction medicine.

[0051] Preferably, in step (5), the bionic material is a bionic cone snail conductive microneedle structure, comprising a microneedle structure and a suction cup structure arranged at the bottom of the microneedle structure, wherein the length of the microneedle in the microneedle structure is 1-2 mm and the diameter is 0.1-0.3 mm, and the diameter of the suction cup in the suction cup structure is 2-4 mm and the thickness is 0.5-1.5 mm.

[0052] Therefore, the present invention adopts a 3D printed natural conductive medical patch aerogel and a preparation method thereof with the above structure, which has the following beneficial effects: (1) The present invention uses kapok cellulose and carbonized wood blocks as raw materials, which have excellent biocompatibility and environmental friendliness. A variety of conductive treatment strategies make the aerogel have lower density and higher strength. 3D printing technology combined with the concept of bionic bionic structure realizes the bionic structure of aerogel and improves the mechanical properties and conductive properties of the material.

[0053] (2) The bionic structure of the present invention not only optimizes the drug release efficiency, but also enhances the adhesion to the skin and has a wide range of application potential. Through reasonable material selection and preparation process, the effectiveness and stability in practical applications are ensured.

[0054] (3) The aerogel scaffold of the present invention not only has the technical advantages of light weight and high strength, but also shows excellent biocompatibility and drug delivery ability in actual tests. These test results show that the design of bionic cone snail has a significant technical effect on improving the performance of aerogel materials in tissue engineering applications, especially in the field of heart repair and other fields.

[0055] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 A flow chart of the preparation process; Figure 2 This is a simulation of a cone snail; Figure 3 is the SEM image of the bionic structure; Figure 4 It is the mechanical properties of the bionic structure and the bionic mechanics simulation diagram; Figure 5 Figure 2 shows the angiogenesis-promoting properties of modified lignin-based hydrogels; Figure 6 Biocompatibility diagram of modified lignin-based hydrogels. DETAILED DESCRIPTION

[0057] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment. Example 1

[0058] like Figure 1 As shown, a method for preparing a 3D printed natural conductive medical patch aerogel is characterized by comprising the following steps: (1) Preparation of kapok fiber After crushing the kapok with a wall-breaking machine, take 1 gram of the crushed kapok and place it in 100 ml of 1 wt% sodium chlorite solution, and adjust the pH to between 4 and 5 with glacial acetic acid. Stir in a 78°C water bath until the solution turns white, separate the fibers and the suspension by suction filtration, and finally wash with distilled water until the pH of the washing liquid is neutral to obtain kapok fibers.

[0059] (2) Carboxymethylation of kapok fibers for conductive treatment After kapok cellulose was mixed evenly with 100 ml of anhydrous ethanol, 5 g of 50% sodium hydroxide was added and stirred at room temperature for 1 hour. Subsequently, 0.2 g of 50% chloroacetic acid was slowly added and stirred in an oil bath at 60°C for 4 hours. After the reaction was completed, 3 g of glacial acetic acid was added to terminate the reaction, and the product was washed with ethanol, filtered and dried to obtain carboxylated kapok fiber.

[0060] (3) Dissolve 3 g of PEGDA in 6 ml of deionized water, add 9 ml of a 3% carboxymethylated kapok fiber pure water suspension, and disperse evenly by ultrasonication for 1 hour. Precool the mixture at 4°C, slowly add 500 μL of 4% ammonium persulfate (APS) and 50 μL of TEMED in an ice bath, and quickly transfer to the mold. Place the mold on a copper block half immersed in liquid nitrogen. After the mixed solution is completely frozen, store it at -20°C for 48 hours to obtain a composite cellulose ice mold. (4) placing the frozen composite cellulose ice mold in ethanol, and promoting the reconstruction of hydrogen bonds between cellulose chains during the solvent replacement process to form a dense lignin network and obtain a composite cellulose solution; (5) Using 3D printing technology and the concept of bionic structure, the composite cellulose solution was printed into an aerogel scaffold with a fractal tree structure, a honeycomb pore structure, and a spiral fiber structure. Printing settings: the layer thickness was set to 100 μm, the printing speed was 20 mm / s, and the printing temperature was room temperature. The SEM image of the bionic structure is shown in Figure 3 . Example 2

[0061] The optimization process of printing parameters in Example 1: The bionic structure simulates the biological structure in nature to optimize the mechanical and functional properties of the material. The specific steps are as follows: (1) Data collection and preprocessing First, the geometric structure and mechanical property data of various 3D printed aerogels were collected. These data include different printing parameters (such as layer thickness, printing speed, printing path, etc.) and the performance indicators of the final aerogel (such as compressive strength, elastic modulus, etc.). The collected data was preprocessed, including removing outliers, standardization and normalization, to facilitate the subsequent training of deep learning models.

[0062] (2) Deep learning model training The preprocessed data was trained using deep learning algorithms such as convolutional neural networks (CNNs) and generative adversarial networks (GANs). Specifically, tools such as Python and TensorFlow were used to set parameters including the number of convolutional layers, learning rate, and batch size to optimize the design parameters of the aerogel. During the training process, cross-validation was used to ensure the robustness and accuracy of the model, thereby improving the prediction performance of the aerogel.

[0063] (3) Optimized design Based on the predictions of the deep learning model, the geometry and porosity of the aerogel scaffold were optimized. The printing quality was improved by adjusting parameters such as the printing path, layer thickness, and printing speed. Specifically, the design of the bionic cone snail simulates the complex fractal structures found in nature to optimize the mechanical and functional properties of the material. The design of the structure not only enhances the conductivity of the aerogel, but also improves its mechanical properties, making it more suitable for biomedical applications.

[0064] (4) Verification and adjustment The effect of the optimized design was verified by experiments, and the performance indicators of the aerogel scaffolds before and after optimization were compared. The tests included compressive strength, toughness, and conductivity, etc., to ensure that the final aerogel scaffold achieved the best performance. The experimental results showed that the optimized cone snail microneedle structure had better mechanical properties (such as Figure 3 The results show that the biocompatibility and mechanical stability of the final product were significantly improved by further adjusting the deep learning model and design parameters.

[0065] (5) Implementation examples and technical effects In further embodiments, the effectiveness of the optimized design was verified by experiments on mice and rats, and the application effect of aerogel scaffolds in cardiac tissue engineering infarction repair was specifically evaluated (e.g. Figure 5 and Figure 6 The experimental results show that the optimized aerogel scaffold has a good effect in promoting tissue regeneration and can effectively improve the repair ability of infarction medicine. Example 3

[0066] like Figure 2 and Figure 4 As shown, the 3D printed bionic structure in Example 1 is a bionic cone snail conductive microneedle structure, which is as follows: (1) Cone snail microneedle structure Size: The cone snail microneedle is designed to have a size of 20 mm × 10 mm × 5 mm (length × width × height) to meet the needs of minimally invasive drug delivery.

[0067] Microneedle length: The microneedle length is 1.5mm and the diameter is 0.2mm to ensure effective penetration of the skin and achieve drug release.

[0068] (2) Suction cup structure Suction cup diameter: The suction cup has a diameter of 3 mm and a thickness of 1 mm. It is located at the bottom of the microneedle and simulates the natural suction cup structure of the cone snail.

[0069] Suction cup shape: The suction cup adopts a concave-convex design with a wavy surface to increase the surface area in contact with the skin, thereby enhancing the adsorption effect and stability.

[0070] Adsorption holes: Several tiny adsorption holes (pore size of 100μm) are designed on the surface of the suction cup to enhance the adsorption force and improve the sealing performance, thereby promoting the effective release of drugs.

[0071] (3) Microneedle structure Number of microneedles: Each microneedle array contains 5 microneedles arranged in a circular pattern to optimize drug delivery.

[0072] Microneedle shape: Microneedles are designed with a conical shape, and the tip is sharp and tapered to facilitate effective penetration of the skin.

[0073] Microneedle spacing: The distance between microneedles is 1 mm, ensuring that the drug can be evenly distributed during the release process.

[0074] (4) Materials and conductivity: Material selection: Carboxymethylated kapok cellulose is used in the microneedle structure to enhance its biocompatibility and mechanical strength.

[0075] Conductive treatment: Conductive polymer coating is performed on the surface of the microneedle to enhance its conductivity and promote drug release and biological signal transmission.

[0076] (5) Design and preparation of conductive layer 1) Conductive layer material selection: Carbonized kapok: obtained by pyrolysis of kapok cellulose by heating it to high temperatures (usually in the range of 400°C to 800°C) in an inert gas environment, giving it excellent electrical conductivity and mechanical properties.

[0077] Advantages: Carbonized kapok has good biocompatibility, light weight, high specific surface area and excellent conductivity, and is suitable for biomedical applications, especially in microneedles and biosensors.

[0078] Charcoal: A carbonized product obtained by dry distillation of wood, usually prepared at 300°C to 600°C, with good conductivity and chemical stability.

[0079] Advantages: Charcoal not only provides good conductivity, but also increases the overall strength and durability of the conductive layer, while having certain biocompatibility.

[0080] Preparation process of conductive layer: 2) Material preparation: Preparation of carbonized kapok: Select high-quality kapok cellulose, wash and dry it, put it into a tubular furnace, heat it to 500°C under nitrogen protection for carbonization treatment, and maintain this temperature for 2 hours to ensure that the kapok is completely converted into a carbonized product.

[0081] Preparation of charcoal: Select suitable wood, wash and dry it, and then carbonize it in a closed reactor. The temperature is set at 400℃ and maintained for 2 to 4 hours to obtain uniform charcoal particles.

[0082] Preparation of conductive layer: Mix the carbonized kapok and charcoal in a certain ratio (1:2) to ensure full uniformity. The mixing ratio can be adjusted according to the required electrical conductivity and mechanical properties.

[0083] An appropriate amount of biocompatible adhesive (such as polyvinyl alcohol or polylactic acid) is added to enhance the adhesion and overall stability of the hybrid material.

[0084] Coating and molding: The mixed conductive material is made into a slurry, and it is evenly coated on the surface of the microneedle by coating or spraying. It is placed at room temperature for 24 hours to promote the evaporation of water and form a firm structure of the conductive layer.

[0085] Finally, the microneedles coated with the conductive layer were placed in an oven and baked at 60°C for 1 hour to further improve the stability and conductive properties of the layer.

[0086] Therefore, the present invention adopts a 3D printed natural conductive medical patch aerogel with the above structure and a preparation method thereof. By introducing bionic structural concept design, bionic structure and 3D printing technology, and combining deep learning algorithm optimization, the latest natural conductive material aerogel is expected to achieve significant improvements in light weight, high strength and functionality, meeting the needs of tissue engineering repair and regenerative medicine, and is particularly suitable for tissue engineering infarction repair in rats.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A 3D printed natural conductive medical patch aerogel, characterized by: It includes ordered micrometer-scale honeycomb pores prepared by freeze casting and a lignin conductive network formed by carbonization treatment.

2. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 1, characterized in that: The following steps are involved: (1) Preparation of kapok fiber, carbonized wood block and carbonized fiber; (2) treating one or more of kapok fiber, carbonized wood block or carbonized fiber to be conductive; (3) mixing the kapok fiber, carbonized wood block or carbonized fiber after the conductive treatment with a polymer precursor solution, and then adding an initiator and a catalyst to polymerize to obtain a mixed solution, and adding the mixed solution into a mold for freeze casting to obtain a composite cellulose ice mold; (4) placing the frozen composite cellulose ice mold in a freezing solvent for hydrogen bond reconstruction to obtain a composite cellulose solution; (5) The composite cellulose solution is 3D printed and coated with a conductive layer to obtain a bionic material.

3. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 2, characterized in that: In step (1), the kapok is crushed and placed in a sodium chlorite solution, and the pH is adjusted to between 4 and 5 with glacial acetic acid. The solution is stirred in a water bath at 75 to 80° C. until the solution turns white, and then filtered to wash the solid matter to obtain kapok fibers.

4. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 2, characterized in that: In step (1), the wood block is cut into small pieces, heated to 600-800° C. in an inert atmosphere for carbonization to obtain carbonized wood blocks; the kapok is heated to 600-800° C. in an inert atmosphere for carbonization to obtain carbonized fibers.

5. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 2, characterized in that: In step (2), the conductive treatment process adopts at least one of the following methods: carboxymethyl modification, conductive polymer coating, metal nanoparticle doping, carbon nanotube or graphene doping, enzyme-catalyzed conductive modification, ionic liquid doping, nitrogen-doped carbonization, graphene oxide reduction treatment, self-assembled monolayer modification, electrochemical doping, plasma treatment, microwave-assisted modification, and electrospray deposition.

6. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 2, characterized in that: In step (3), PEGDA is dissolved in deionized water to obtain a polymer precursor solution, kapok fibers, carbonized wood blocks or carbonized fibers after conductive treatment are added to water to form a suspension, the suspension is added to the polymer precursor solution for ultrasonic dispersion to obtain a mixed solution, the mixed solution is pre-cooled at 4°C, and an initiator and a catalyst are slowly added in an ice bath, and the mixture is quickly transferred to a mold, and the mold is placed on a copper block half immersed in liquid nitrogen. After the mixed solution is completely frozen, it is stored at -20°C for 48 hours to obtain a composite cellulose ice mold.

7. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 6, characterized in that: In step (3), the mass volume ratio of PEGDA to deionized water is 1-5 g: 2-10 mL, the kapok fiber, carbonized wood block or carbonized fiber after conductive treatment is 1-5% of the mass of the suspension, the initiator is ammonium persulfate, the catalyst is tetramethylethylenediamine, and the volume ratio of the initiator to the catalyst is 10-20:1-2.

8. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 2, characterized in that: In step (4), the freezing solvent is ethanol or acetone.

9. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 2, characterized in that: In step (5), the 3D printing parameters are: room temperature, layer thickness of 50-150 μm, and printing speed of 5-25 mm / s.

10. The method for preparing a 3D printed natural conductive medical patch aerogel according to claim 2, characterized in that: In step (5), the bionic material is a bionic cone snail conductive microneedle structure, including a microneedle structure and a suction cup structure arranged at the bottom of the microneedle structure, wherein the length of the microneedle in the microneedle structure is 1-2 mm and the diameter is 0.1-0.3 mm, and the diameter of the suction cup in the suction cup structure is 2-4 mm and the thickness is 0.5-1.5 mm.

Citation Information

Patent Citations

  • Conductive hydrogel with anisotropic mechanical and electrical characteristics as well as preparation method and application of conductive hydrogel

    CN116925391A

  • Cotton fiber dissolution and regeneration and 3D printing of cellulose based conductive composites

    US20170140848A1

  • Electroconductive hydrogel and devices with conducting polymers assembled around a 3D nanofiber framework

    US20240263002A1

  • Improvements relating to hydrogels and aerogels

    WO2023031289A1